A New Species of Ceratosolen (Agaonidae) Associated With Ficus hispida L. and Proposed Changes in Status of Two Other Pollinator Fig Wasps - Wong, Da-Mien; Fan, Songle; Compton, Stephen G.; Yu, Hui (Indian Journal of Entomology, 2023)
An increasing number of fig trees are known to support more than one species of pollinator fig wasp (Agaonidae). This brings into question the relative importance of co-evolution, radiation and host switching in the development of this mutualistic association. The functionally dioecious Ficus hispida has a wide distribution in Asia. It supports at least three morphologically distinct Ceratosolen pollinators, one of which we describe as C. abscondus Wong & Yu sp. n., based on collections in China and Thailand. The other two taxa were originally described as separate species, but subsequently downgraded to sub-species. The morphological differences between the three taxa are similar in extent to those recorded between other Ceratosolen species and we therefore re-instate them as the distinct species, C. solmsi (Mayr) and C. marchali (Mayr). An identification key is provided to distinguish between them and relationships between Ficus species and their Ceratosolen pollinators of this and related species are discussed.